The Effect Of Sustainability Reporting Disclosure Based On Global Reporting Initiative (GRI) G4 On Company Performance (A Study On Companies Listed In Indonesia Stock Exchange) - EINDE Evana (The Indonesian Journal of Accounting Research, 2017)
Abstract: This research aims to analyze the effect of sustainability report disclosures which are variables of economic dimension, environment dimension and social dimension variables on company performance (Tobin’s Q). The index used as a guideline sustainability report disclosure in this research is based on the Global Reporting Initiative (GRI) G4. The population in this research is the entire companies listed in Indonesia Stock Exchange in 2014-2015. The companies as the sample are based on the purposive sampling method chosen by some specific criteria. Type of data used in this research is secondary data. Data analysis uses multiple linear regression method using SPSS 22 as an analytical tool. The result of this research shows that the variable of economic dimension has a positive effect on company performance. On the other hand, variables of environment dimension and social dimension do not affect the company performanceAbstrak: Penelitian ini bertujuan untuk menganalisis pengaruh pengungkapan laporan keberlanjutan yang merupakan variabel dimensi ekonomi, dimensi lingkungan dan variabel dimensi sosial terhadap kinerja perusahaan (Tobin's Q). Indeks yang digunakan sebagai pengungkapan laporan keberlanjutan panduan dalam penelitian ini didasarkan pada Global Reporting Initiative (GRI) G4. Populasi dalam penelitian ini adalah seluruh perusahaan yang terdaftar di Bursa Efek Indonesia pada tahun 2014-2015. Perusahaan sebagai sampel didasarkan pada metode purposive sampling yang dipilih oleh beberapa kriteria tertentu. Jenis data yang digunakan dalam penelitian ini adalah data sekunder. Analisis data menggunakan metode regresi linier berganda menggunakan SPSS 22 sebagai alat analisis. Hasil penelitian menunjukkan bahwa variabel dimensi ekonomi berpengaruh positif terhadap kinerja perusahaan. Di sisi lain, variabel dimensi lingkungan dan dimensi sosial tidak berpengaruh pada kinerja perusahaan.